2001
DOI: 10.1053/rmed.2001.1050
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-associated activation markers in healthy smokers relates to a fall in DLCOand to emphysematous changes on high resolution CT

Abstract: Smoking is a risk factor for developing chronic obstructive pulmonary disease (COPD), but there are no good indicators for early identification of subjects who will develop symptomatic COPD. The aim of this study was to investigate inflammatory mechanisms related to changes in lung function and emphysematous changes on high resolution computed tomography (HRCT) in 'healthy' smokers. Subjects were 60-year-old men from a population study. Bronchoscopy was performed in 30 smokers and 18 who had never smoked. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 37 publications
3
88
0
Order By: Relevance
“…Men 60 years of age were recruited from the randomized population study "Men born in Gö teborg in 1933" (19,20 ). A subset of the study population of 879 participants volunteered to undergo fiberoptic bronchoscopy at the age of 60.…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Men 60 years of age were recruited from the randomized population study "Men born in Gö teborg in 1933" (19,20 ). A subset of the study population of 879 participants volunteered to undergo fiberoptic bronchoscopy at the age of 60.…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
“…sampling BAL sampling was carried out under standard conditions (20 ) with the informed consent of the individuals, and the studies were approved by the ethics committees of the Sahlgrenska Hospital (Gbg M 117-01) and Lund University Hospital in Sweden (LU 689-01). After sampling, the BAL fluid was immediately transported on ice to the laboratory for processing and storage at Ϫ80°C (20 ).…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of a limited number of cross-sectional studies of biomarkers in BAL or sputum in subjects with COPD-E phenotyped by CT scan, including studies from our group 16,17 and others, [24][25][26] but none of these studies has evaluated changes in biomarkers of infl ammation over time in relation to changes in the extent of COPD-E on chest CT scan in subjects with COPD-E who have quit smoking. A longitudinal study by Parr et al 27 of may have emphysematous lesions on CT scan 28 and, thus, be misclassifi ed if only pulmonary function studies and not CT scans are performed. Chest CT scans are providing an important method of documenting the extent of emphysema and have demonstrated that the area of the lung with chest CT scan attenuation values below 2 910 HU and 2 950 HU correlates signifi cantly with macroscopic 29 and microscopic 30 pathologic features of emphysema.…”
Section: Cotinine Assay and History Of Quitting Cigarette Smokingmentioning
confidence: 99%
“…Participants provided informed consent. BAL sampling was carried out under typical conditions (10 ), and the BAL fluid was immediately transported on ice to the laboratory for processing and storage at Ϫ80°C (10 ). The protein concentrations in the recovered BAL were measured by use of Coomassie plus protein assay reagent (Pierce) with bovine serum albumin as a reference (14 ).…”
Section: Bal Samplingmentioning
confidence: 99%